Degnifying of the Indigenous: An Introduction to the Traditional Law of Indigenous People - saeed habiba; Behnam Habibi (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2014)
AbstractThe term ''Folklore'' verbally means public and people's culture. Expressions orsymbols of folklore include productions, works, creativity, believes and traditions ofa group or a definite society which have been flourished and emerged via tangibleor intangible ways, in the form of artistic (either performances or nonperformances)or literary works or in the form of indigenous knowledge (includingmedical, agricultural and environmental science) and natural and ecologic sources.These factors have always been the instrument of recognizing the communities andalso have been the cultural, biological and historical identity of such societies. Inthis essay, along with the clarifying the concept and historical background offolklore expressions, three traits of folklore, including the oldness, belonging to acertain territory and collectivity, will be studied. However, in association with theidentity of folklore, three theories are propounded, including ''sui generis'', ''exploitation right'' and ''property right'', in which collective property right isaccepted and finally the abstractness of relationship between creators and owneragainst aspects of folklore is regarded as acceptable.